The impact of natural disasters on the elderly - Cherniack, MD, E. Paul (American Journal of Disaster Medicine, 2008)
Objective: To review and draw conclusions about the impact of natural disasters on the elderly from the published medical literature. Design: Articles were obtained by searching the PubMed database and Google search engines using terms such as “disaster,” “elderly,” “hurricane,” “tornado,” “earthquake,” and “flood.” More articles were obtained from the reference lists of those obtained in the initial search. Results: Forty-five journal articles were reviewed. Conclusions: Many, but not all, studies have found that older individuals are more likely to suffer adverse physical consequences. This is not surprising considering the elderly are more likely to be in worse health before disasters and less able to seek assistance afterward. The lack of agreement between studies is not surprising either, considering heterogeneity in disasters, populations, and survey methods. This heterogeneity also precludes determination as to whether older individuals have a worse or more favorable psychological outcome than younger individuals. Several investigations, however, have noted that individuals may be more resilient to some of the psychological manifestations of disasters with more frequent exposure, often including the elderly. Many suggestions have been proposed to address the potential needs of older individuals such as involving existing organizations and those with existing geriatric expertise to design disaster plans, develop education, communication systems, and warnings for people with sensory impairment, create new methods for identifying, tracking, and following older individuals, and make special arrangements to provide disaster-related aid. However, there are only anecdotal reports of the success of the application of such methods.